2015
DOI: 10.1002/cphc.201500033
|View full text |Cite
|
Sign up to set email alerts
|

NMR Crystallography of an Oxovanadium(V) Complex by an Approach Combining Multinuclear Magic Angle Spinning NMR, DFT, and Spin Dynamics Simulations

Abstract: Bioinorganic vanadium(V) solids are often challenging for structural analysis. Here, we explore an NMR crystallography approach involving multinuclear (13) C/(51) V solid-state NMR spectroscopy, density functional theory (DFT), and spin dynamics numerical simulations, for the spectral assignment and the 3D structural analysis of an isotopically unmodified oxovanadium(V) complex, containing 17 crystallographically inequivalent (13) C sites. In particular, we report the first NMR determination of C-V distances. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Two channels of conventional NMR probes cannot be tuned simultaneously to such close Larmor frequencies. However, this instrumental limitation can be circumvented by the use of the REDOR box hardware, commercialized by NMR Service GmbH (Pourpoint et al, 2012(Pourpoint et al, , 2013(Pourpoint et al, , 2014(Pourpoint et al, , 2015Li et al, 2014;Hirsemann et al, 2011). When this frequency splitter is connected to one channel of an NMR probe, this channel can be tuned and matched simultaneously to two close Larmor frequencies, such that those corresponding to the 13 C and 27 Al isotopes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two channels of conventional NMR probes cannot be tuned simultaneously to such close Larmor frequencies. However, this instrumental limitation can be circumvented by the use of the REDOR box hardware, commercialized by NMR Service GmbH (Pourpoint et al, 2012(Pourpoint et al, , 2013(Pourpoint et al, , 2014(Pourpoint et al, , 2015Li et al, 2014;Hirsemann et al, 2011). When this frequency splitter is connected to one channel of an NMR probe, this channel can be tuned and matched simultaneously to two close Larmor frequencies, such that those corresponding to the 13 C and 27 Al isotopes.…”
mentioning
confidence: 99%
“…The heteronuclear 13 C-27 Al dipolar couplings are then reintroduced, under MAS for resolution purpose, by applying on the 13 C channel a Simultaneous Frequency and Amplitude Modulation (SFAM 1 ) recoupling scheme (Fu et al, 1997;Lafon et al, 2009;Lu, Lafon, Tré bosc, Tricot et al, 2012). This recoupling has already been incorporated into the RESPDOR scheme (Pourpoint et al, 2012(Pourpoint et al, , 2013(Pourpoint et al, , 2015 and the sequence is denoted SFAM-RESPDOR. The SFAM 1 heteronuclear recoupling has been chosen because it is robust and efficient when the irradiated spins are not subjected to large homonuclear dipolar couplings, as is the case for the 13 C nuclei in this isotopically unmodified MIL-53(Al).…”
mentioning
confidence: 99%
“…Such an adjustment was proposed for the S-RESPDOR experiment in 2012, 15 where 13 C- 27 Al distances were measured by splitting the saturation pulse applied on 27 Al into two equal parts, and fitting the  pulse on 13 C in the gap. This work paved the way for S-RESPDOR distance measurement experiments to be used for systems with close Larmor frequencies, such as the first 51 V- 13 C distance measurement by NMR 16 . Additional studies demonstrated correlation measurements between nuclei with close Larmor frequencies such as DNP enhanced 27 Al-13 C 2D D-HMQC that was used for probing the structure of a metal-organic framework material 17 , and 27 Al- 13 C HETCOR D-HMQC and J-HMQC 2D experiments conducted on two co-catalysts that have importance for the polymerization process of olefins 18 .…”
Section: Introductionmentioning
confidence: 99%
“…[17,20] Despite these difficulties, penta-coordinated Sc sites have been recently observed by solid-state NMR spectroscopy in Sc-doped BaZrO 3 containing oxygen vacancies. Therefore, to the best of our knowledge, 13 CÀ 45 Sc double resonance experiments have not been reporteds of ar.N evertheless,w eh ave demonstrated recently that the use of af requency splitter [23] can circumventt his limitation since this device allows tuning and matching as ingle probe channel to two close frequencies.W e have notably used such ad evice to acquire double-resonance 27 AlÀ 13 C [24,25] and 13 CÀ 51 V [26] solid-state NMR data. [6,15] The NMR observation of carbon-scandium proximities would also provide valuablei nformation aboutt he structure of Scbased MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we have demonstrated recently that the use of a frequency splitter can circumvent this limitation since this device allows tuning and matching a single probe channel to two close frequencies. We have notably used such a device to acquire double‐resonance 27 Al− 13 C and 13 C− 51 V solid‐state NMR data.…”
Section: Introductionmentioning
confidence: 99%